Friction stir processing of Al/B4C nanocomposites prepared by Stir-Ultrasonication casting method. (2022) - Krishnan, Parthiban; Lakshmanan, Poovazhagan; Palani, Sarangapani; Arumugam, Arun; Kulothungan, S
Abstract: AA6061/B4 C metal matrix nanocomposites (AMMNCs) were synthesized in this research using stir casting with the assistance of ultrasonication. Due to the challenges of integration, dispersion, and interfacial wetting during stir-casting, ultrasonication is regarded as an alternate method for increasing the mechanical characteristics of metal matrix by distributing nanoparticles more evenly. From the castings, 6 mm thick plates were produced, and friction stir processing (FSP) has been successfully carried out. FSP was performed with the tool rotating at a rate of 1000 revolutions per minute, an axial force of 10 kN, and a stir velocity is 80 mm/min. A tool with a square pin profile was fabricated using high carbon and high chrome steel. Optical and scanning electron microscopy was used to examine the microstructures. Fine granules and uniform dispersion of Particles of B4 C were identified in the FSP zone. Microhardness and ultimate strength of the FSP AMMNCs were significantly increased as compared with monolithic alloy and un-processed AMMNCs.